Research on the impact of international agreements and standards on national legal systems and legal order - Єфремова, Наталя Володимирівна; Єфремова, Н. В.; Yefremova, Natalia V.; Баймуратов, Михайло Олександрович; Баймуратов, М. О.; Baimuratov, Mykhailo O.; Кофман, Борис Якович; Кофман, Б. Я.; Kofman, Borys Ya.; Бобровник, Денис Олександрович; Бобровник, Д. О.; Bobrovnyk, Denys O.; et al. (Florencia : Editorial Primmate S. A. S., 2024)
In the contemporary world, where globalization is intensifying, the significance of international agreements and their impact on national legal systems is increasing. International agreements serve not only as the foundation for regulating interstate relations but also as a crucial tool for unifying legal norms, promoting the protection of human rights, sustainable development, economic cooperation, and environmental protection. The analysis of theoretical aspects demonstrates that international agreements are a crucial element of the global legal system, providing a basis for international cooperation. Studying the practical application of international agreements in national legal systems has revealed various mechanisms for implementing and adapting international norms to domestic legislation. Discussions on the challenges of compatibility, sovereignty, the effectiveness of international agreements, and the adaptation of international norms to the national context have highlighted the need to balance the requirements of international law with national peculiarities. The study's conclusions emphasize the importance of integrating global norms from international agreements into national legal systems. Further research should focus on developing flexible mechanisms for implementing international agreements that consider the specificities and needs of different states. Additionally, it is important to analyze the impact of technological development on international law. У сучасному світі, де глобалізація посилюється, значення міжнародних договорів та їх вплив на національні правові системи зростає. Міжнародні угоди служать не лише основою регулювання міждержавних відносин, але й важливим інструментом уніфікації правових норм, сприяння захисту прав людини, сталому розвитку, економічному співробітництву та охороні навколишнього середовища. Аналіз теоретичних аспектів свідчить про те, що міжнародні договори є найважливішим елементом глобальної правової системи, що є основою для міжнародного співробітництва. Вивчення практичного застосування міжнародних договорів у національних правових системах виявило різноманітні механізми імплементації та адаптації міжнародних норм до внутрішнього законодавства. Дискусії щодо проблем сумісності, суверенітету, ефективності міжнародних угод та адаптації міжнародних норм до національного контексту підкреслили необхідність балансу між вимогами міжнародного права та національними особливостями. У висновках дослідження підкреслюється важливість інтеграції глобальних норм міжнародних угод у національні правові системи. Подальші дослідження слід зосередити на розробці гнучких механізмів імплементації міжнародних угод, які враховують особливості та потреби різних держав. Крім того, важливо проаналізувати вплив технологічного розвитку на міжнародне право.
Baimuratov M. Research on the impact of international agreements and standards on national legal systems and legal order / M. Baimuratov, B. Kofman, D. Bobrovnik et al. // Amazonia Investiga. – Florencia : Editorial Primmate S. A. S., 2024. – 13(74). – P. 90-102. Режим доступу: https://doi.org/10.34069/AI/2024.74.02.8
Keywords: international treaties; national legal systems; globalization; international law; legal integration; sovereignty; effectiveness of international treaties; adaptation of legal norms; міжнародні договори; національні правові системи; глобалізація; міжнародне право; правова інтеграція; суверенітет; ефективність міжнародних договорів; адаптація правових норм